HPTLC Estimation of Harmine from the Stem Bark of Symplocos racemosa Roxb. - Kumar, G.S.; Vrushabendra Swamy, B.M.; Ashoka Babu, V.L.; Chandanam, Sridhar; Sreenivasa Rao , T.; Tarakaram, K. (Asian Journal of Chemistry, 2010)
An attempt was made to quantify harmine in different samples of Symplocos reacemosa. Precoated silica gel G (aluminium backed) plates were used as stationary phase and toluene : ethyl acetate : methanol (6 : 2 : 2) was used as mobile phase. Detection and quantification were performed by densitometry at λ 324 nm. The linear range was 100 to 500 ng. The proposed HPTLC method was found to be reproducible, accurate and precise.